A New Fuzzy H∞ Filter Design for Nonlinear Time-Delay Systems with Mismatched Premise Membership Functions*. Issue 1 (July 2017) - Ma, Qianqian; Li, Li; Ma, Guangcheng; Jia, Daling; Xia, Hongwei
Abstract: This paper is concerned with the fuzzy H ∞ filter design issue for nonlinear systems with time-varying delay. To overcome the limitations of conventional methods with matched preconditions, the filter to be designed and the T-S fuzzy model are assumed to have different premise membership functions and different number of rules. Hence, greater design flexibility can be obtained. Moreover, in order to reduce conservatism, a novel integral inequality which is tighter than the traditional inequalities derived from the Leibniz-Newton formula is applied. Furthermore, the proposed filter design approach also considered the information about the membership functions, which can help further relax the derived results. Finally, two numerical examples are provided to demonstrate the effectiveness and superiority of the proposed method.